ANALISIS KEADILAN ORGANISASI (ORGANIZATIONAL JUSTICE) DAN DAMPAKNYA PADA MOTIVASI KERJA - Putrie, Rena Augia; Muyasaroh, Muyasaroh; Islami, Nurul Ariffaeni; Rosyid, Bahrur; Setiawan, Arief (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the influence of organizational justice on employee work motivation. Organizational justice is considered a crucial factor in shaping employee attitudes and behavior, particularly work motivation, which plays a role in improving organizational effectiveness and performance. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees in the organizations studied. Organizational justice was measured through three dimensions: distributive justice, procedural justice, and interactional justice. Work motivation was measured through indicators of work enthusiasm, responsibility, and achievement drive. The data were analyzed using simple linear regression analysis. The results showed that organizational justice had a positive and significant effect on employee work motivation, both partially and simultaneously. This finding indicates that the higher employees' perceptions of justice implemented within the organization, the higher their work motivation. Interactional justice had the most dominant influence compared to other justice dimensions. The conclusion of this study confirms that the consistent implementation of organizational justice can increase employee work motivation. Therefore, organizations are advised to consider aspects of justice in their human resource management policies and practices to create a conducive and motivating work environment.